Impacto psicosocial de la modalidad de estudios híbrida “distancia-virtual-semipresencial”, caso carrera de Medicina Veterinaria en la ESPAM MFL, periodo 2021 - Intriago Zambrano, María Victoria (2023)
Due to the social confinement during the period 2021, in the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, hybrid study modalities "distance-virtual-semipresential" were implemented to give continuity to the educational process, facing new challenges and challenges that affected the teaching-learning process of the student body. The objective of this research was to evaluate the impact of the hybrid study modality "distance-virtual-semipresential" on the psychosocial development of the students of the Veterinary Medicine Career of the ESPAM MFL during the 2021 academic period, in order to make academic decisions. The methodological strategy responds to field research, descriptive and documentary, systematized with deductive and inductive methods, by means of survey and interview techniques. The results showed that there is a high rate of students with psychosocial affectations as a result of the changes chosen by the institution and a poor understanding of the knowledge imparted, as evidenced by the low academic performance of the students; however, there is also evidence of great technological advances, since both students and teachers were forced to adapt to this new teaching-learning style. In conclusion, Latin America and Ecuador were not prepared to face distance education. In view of this situation, an action plan was developed and proposed, taking into consideration the weaknesses and strengths found in the results of the field research, which was based on dimensions that displayed a series of indicators with psychosocial risk problems.